(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The discovery of the therapeutic properties of penicillin, combined with its industrial production in the usa, raised a strong interest in many countries to succeed in the acquisition of this novel antimicrobial which showed exceptional results in its clinical use. In Mexico, its introduction played a role in the profound epidemiological transition from 1940 to 1960, which in the present paper is analyzed from the point of view of two periods: that of the pre-penicillin and that of the post-penicillin one.